A Pharmacological study on the possible influence of Diphenyl Dimethyl Bicarboxylate (DDB) on behavior of psychologically stressed normally- fed and protein malnourished mice - Fatma Mahmoud Sabry; Mohamed Raouf Hamed; Mostafa Elsayed Elsayed (Cairo : Fatma Mahmoud Sabry, 2014)
The aim of the present study was to investigate the possible neurobehavioral effects of DDB on psychologically stressed protein malnourished mice as compared to its effect in normally fed ones. The work was implemented on mice, fluoxetine was used as a reference drug. Animals were divided to two major groups, a normally fed group provided with a 20% protein diet (NF) and a protein malnourished one, which was provided with a diet containing 8% protein (PM) for 21 days feeding with synthetic diet, was applied along the whole period of the experiment. Stress was induced using the learned helplessness technique (LH). After completion of 21 days under the synthetic diet regimen each animal was exposed to 5 days of the psychological stress session (LH) either alone or in association with drug administration. Drugs (DDB or fluoxetine) were administrated before foot shocks daily. DDB was administrated in dose of 100 mg/kg p.o. and fluoxetine in dose of 10 mg/kg i.p
Thesis (M.Sc.) - Cairo University - Faculty of Pharmacy - Department of Pharmacology and Toxicology
Issued also as CD
Keywords: DDB; Pharmacological stress; Protein malnourished